Evaluación del consumo de portadores energéticos en el proceso productivo de la empresa Familia Sancela del Ecuador en el año 2013. Propuesta mejora de la eficiencia energética en el proceso de fabricación de papel. - Berrazueta Vallejo, Pedro Pablo (2015)
The present investigation has as objective to lower the energy index (MW / ton of paper produced), which presents a diagnosis of the current situation of the electric, thermal energy consumption. or what is carried out a census of the most important and representative loads in the area of Factory "Mills." Also for the above-mentioned he/she is carried out an action plan in which is included the possible solutions for an efficient use of energy. It is described like it is detected the best possibilities of energy saving in which is included their economic justification and their impact in the optimization of the processes. According to the analysis and the alternatives proposals he/she improved the energy efficiency, starting from the implementation of the projects of improvement analyzed in the investigation, helping to that the system obtains a monthly reduction of energy of 220 MW, the Index energy first floor of 4.83 at 4.61 MW/ton, obtaining a reduction of 4.5% of this energy indicator, for a total saving in the implementation of 272625, 88 USD/year.